Inverted T bypass: a solution for distal revascularization in the absence of an adequate autologous vein graft. - Armanda Duarte; Tony R. Soares; Gonçalo Cabral; Tiago Costa; José Tiago; José Gimenez; Diogo Cunha e Sá (Angiologia e Cirurgia Vascular, 2023)
Introduction: Peripheral arterial disease has become a worldwide problem, with chronic limb-threatening ischemia(CLTI) being its most extreme manifestation. Recently, endovascular strategies evolved and became the first approach in many revascularization procedures. However, infrapopliteal (IP) disease is still a therapeutic challange.1–3